PENGEMBANGAN MEDIA MISTERY BOX UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS II SD IT AL-IHSAN - Ahmad Ilham Asmariyadi; Raimon Efendi; Arda Sulistika Andre (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by problems and obstacles in learning, such as the minimal use of media, especially in Indonesia language subject. Learning that uses media is really needed to support learning activities so that learning objecctives are achieved. So the effort made was to develop the Mystery Box learning media on the material of recognizing feelings in class II of elementary school. So that it helps teacher and students in carrying out the teaching and learning process. The research method used in this research is the research and development (R&D) method. The model used is the ADDIE model which consists of five stages of analyze, design, development, implementation, evaluation.The result of the Mystery Box media validation werw assessed by 4 (four) expert validators, namely the material validator results with an average og 82,5% were categorized as valid. The design validation results werw 85% categorized as valid. Language validation result with an average of 95% are categorized as valid. The results of the validator questions with was assessed by one teacher, obtained an average of 97,5% wihich was categorized as very practical. Basedon the test results,student responses reached 97,38%, which wa categorized as very practical. The results of the learning effectiveness assessment for class II student obtained an average of 85,71% categorized as very effective.